The Imaginary Colliery Project: The Future of Tourism in Crowsnest Pass - Rogers, Scott (UnderCurrents: Journal of Critical Environmental Studies, 2007)
This work specifically examines a transition from resource based industries to a tourism economy in the Crowsnest Pass. The Imaginary Colliery Project proposal complicates this movement from mining to tourism and suggests that authentic histories, architecture and culture can be fabricated to suit the necessities of tourist industries.